Silicon carbide biotechnology : a biocompatible semiconductor for advanced biomedical devices and applications - Saddow, Stephen E. (Elsevier, 2012)
Silicon Carbide (SiC) is a wide-band-gap semiconductor biocompatible material that has the potential to advance advanced biomedical applications. SiC devices offer higher power densities and lower energy losses, enabling lighter, more compact and higher efficiency products for biocompatible and long-term in vivo applications ranging from heart stent coatings and bone implant scaffolds to neurological implants and sensors. The main problem facing the medical community today is the lack of biocompatible materials that are also capable of electronic operation. Such devices are currently implement.